Understanding multiple perspectives on social value in business: an integrative review and typology - Cruz Jara, Marcelo Francisco de la (Journal of business ethics, 2025)
Although the concept of social value has been present in business literature for over a century, it lacks definitional consensus, is often imprecise, and has not been sufficiently theorized. With social value becoming more prevalent across business scholarship domains, the lack of conceptual clarity and consistency hampers substantive research progress. We conduct an integrative review of 288 articles drawn from 60 peer-reviewed journals covering a wide spectrum of business domains. We synthesize the review findings into a polythetic typology that identifies five distinct approaches to understanding and managing social value in business. The proposed typology of social value organizes and consolidates the theoretical and conceptual heterogeneity of the social value concept providing much-needed clarity and structure for future research. It allows scholars to structure and unify various conceptualizations into a more holistic yet nuanced understanding, and the necessary (but currently lacking) clarity to enable new theorizing and guide future research. The proposed typology further offers new ways of thinking about social value and provides direction to managerial practice on the desirability and feasibility of implementing different social value approaches into firms’ core business operations and strategies.